Related Factors, Causes and Stress Respons of Hypertension Patients in Coastal Communities: Mixed Method - Atoy, Lena; Tahir, Rusna; Rini, Dewi Sartiya; Pertami, Sumirah Budi (Poltekkes Kemenkes Palu, 2023)
Hypertension is a non-communicable disease (NCD) that is now a health problem that is difficult to control in number and is the cause of high mortality and morbidity rates globally. In addition to the prevalence of events that are increasing over time, hypertension is also known to be dangerous because it is a risk for other chronic diseases such as heart disease and stoke disease. This study aims to analyze the incidence and related factors of hypertension in coastal communities in Motui District, North Konawe Regency, Southeast Sulawesi Province. The research design uses a mix of quantitative and qualitative methods. Quantitative methods use cross-sectional while quantitative methods by determining themes. The sample in the study was 60 people with hypertension. Sampling technique with non probability sampling with consecutive sampling method. The results showed that 44 people (73.3%) experienced severe stress and 16 people (26.7%) experienced moderate stress. Some factors that cause stressful events are gender (p = 0.002), and occupation (p = 0.000). The cause of stress experienced is due to the heavy workload, economic difficulties and personal problems. While the response of hypertension patients who experience stress is anger, anxiety and pressure and crying. The conclusion of this study is that people with hypertension experience severe stress caused by workload, economic and personal problems.